Trajectories of psychological distress during the COVID‐19 pandemic among community‐dwelling older adults in Quebec: A longitudinal study. (26th January 2023) - Matovic, Sara; Grenier, Sébastien; Jauvin, Florence; Gravel, Catherine; Vasiliadis, Helen‐Maria; Vasil, Nancy; Belleville, Sylvie; Rainville, Pierre; Dang‐Vu, Thien Thanh; Aubertin‐Leheudre, Mylène; Knäuper, Bärbel; Dialahy, Isaora Zefania; et al.
Abstract: Objective: The COVID‐19 pandemic and its associated public health measures may increase the risk for psychological distress among vulnerable older adults. This longitudinal study aimed to identify predictors of psychological distress trajectories among community‐dwelling older adults in Quebec, Canada. Methods: The study spanned four time points across 13 months and three waves of the COVID‐19 pandemic. The sample included 645 community‐dwelling older adults ages 60 years and older in Quebec. Participants completed telephone‐based interviews that included the Kessler 6‐item Psychological Distress Scale (K6) to assess psychological distress at each time point as well as information on socioeconomic, medical, psychological and COVID‐19 related factors. Group‐based trajectory modelling was used to identify distinct trajectories of psychological distress across time. Results: Three group‐based trajectories of psychological distress were identified: the resilient (50.5%), reactive (34.9%), and elevated distress groups (14.6%). Individuals with mobility issues, insomnia symptoms, COVID‐19 related acute stress, general health anxiety, increased loneliness symptoms, and those unable to use technology to see others were more likely to be in the reactive and elevated groups than the resilient group. Those with past mental health problems had uniquely increased odds of being in the reactive group compared to the resilient group. Individuals living in poverty and those who reported taking psychotropic medication had increased odds of being in the elevated distress group compared to the resilient group. Conclusion: These findings characterized distinct trajectories of psychological distress in older adults and identified risk factors for elevated distress levels. Key points: On average psychological distress was stable during the first 9 months of the COVID‐19 pandemic, but increased at the 13‐month assessment. Using group‐based trajectory modeling, three distinct trajectories of psychological distress were identified: (1) resilient; (2) reactive; and (3) elevated distress. Individuals with mobility issues, insomnia symptoms, COVID‐19 related acute stress, general health anxiety, increased loneliness symptoms, and those unable to use videoconferencing technology were more likely to be in the reactive and elevated distress groups than the resilient group. Although most older adults experienced relatively low levels of psychological distress, it was estimated that about 14.6% reported elevated distress throughout the pandemic.